"Technology Doesn't Judge You": Young Australian Women's Views on Using the Internet and Smartphones to Address Intimate Partner Violence. Issue 3 (3rd July 2017) - Tarzia, Laura; Iyer, Deepthi; Thrower, Emily; Hegarty, Kelsey
ABSTRACT: Intimate partner violence (IPV) is a pervasive social issue. Younger women tend to experience the highest rates of violence, associated with a range of negative health outcomes. Although interventions in health settings have shown promise, younger women may be reluctant to access services or discuss relationships with a health professional. Delivering an IPV intervention online or via a smartphone has the potential to overcome some of these barriers. Little is known, however, about how young women might perceive such an intervention, or what factors might influence its uptake. Drawing on focus groups interviews, we explore the views of young Australian women on using a website or application to address IPV. Azjen's Theory of Planned Behavior is used to help understand the beliefs and norms around technology and help-seeking for IPV. Findings highlight the potential for technological interventions to become a valuable addition to the resources available to young women.